Identification and Analysis of Phenolic Compounds in Vaccinium uliginosum L. and Its Lipid-Lowering Activity In Vitro - Ying Zhang; Wenjiang Dong; Manjun Zhao; Jiyue Zhang; Li Li; Yan Ma; Xianjun Meng; Yuehua Wang (Foods)
Vaccinium uliginosum L. (VU), rich in polyphenols, is an important wild berry resource primarily distributed in extremely cold regions. However, the detailed composition of Vaccinium uliginosum L. polyphenols (VUPs) has not been reported, which limits the development and utilization of VU. In this study, VU-free polyphenols (VUFPs) and VU-bound polyphenols (VUBPs) were, respectively, extracted using an ultrasonic, complex enzyme and alkali extraction method; the compositions were identified using ultra-performance liquid chromatography–electrospray ionization mass spectrometry, and lipid-lowering activity in vitro was evaluated. The results showed that 885 polyphenols and 47 anthocyanins were detected in the VUFPs and VUBPs, and 30 anthocyanin monomers were firstly detected in VU. Compared with the model group, the accumulation of lipid droplets and the total cholesterol and triglyceride contents in the high-concentration VUP group reduced by 36.95%, 65.82%, and 62.43%, respectively, and liver damage was also alleviated. It was also found that VUP can regulate the level of Asialoglycoprotein receptor 1, a new target for lipid lowering. In summary, this study provides a detailed report on VUP for the first time, confirming that VUP has lipid-lowering potential in vitro. These findings suggest new strategies and theoretical support for the development and utilization of VU, especially in the field of functional foods.